SISTEM PENDUKUNG KEPUTUSAN DALAM MEREKOMENDASIKAN TEMPAT LES MUSIK DIPEMATANGSIANTAR MENGGUNAKAN METODE MULTIFACTOR EVALUATION PROCESS (MFEP) - Siburian, Theresia; Dewi, Rafiqa; Widodo, Widodo (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2018)
Keroncong, Pop, Dangdut, and Hip Pop. Music is basically to entertain and express themselves from feelings of sadness or happiness. Along with the increasing popularity of music, a lot of music lessons were made especially in Pematangsiantar. This makes consumers confused and needs information to decide which music lessons are suitable for their needs. So the author uses a Decision Support System with the Multi-Factor Evaluation Process (MFEP) method to facilitate decision making. MFEP is a method with emphasis on various factors and criteria that perform the calculation of weighting system where the calculation will be valuable for each factor that affects the decision making of data data to be processed. The MFEP method is also called a scaled score that requires a comparative norm to be interpreted qualitatively and this makes the advantages of the MFEP method. The previous criteria were Criteria Place C1 (C1), Music Facilities Criteria (C2), Price Criteria (C3), Criteria Schedule / time guidance (C4), Employee Service Criteria (C5). By using 4 Alternative Place of Music Les existed memematangsiantar include: Legato Art Center, Era Music Siantar, Grace Music Studio, C and C Music Education. Results of recommendation of Decision Support System in Recommending Place Les Music dipematangsiantar using method MFEP (Multifactor Evaluation Process). Which we write with first rank that is Legato Art Center .Â  It is expected that this research can help the consumer to get the right recommendation in choosing the place of music lesson in accordance with the cost of music lesson and music quality.Keywords: Decision Support System, Multi-Factor Evaluation Process, ranking, Music